SIMULASI ELECTRONIC ROAD PRICING BERBASIS GLOBAL POSITIONING SYSTEM - David David; Sunarto Sunarto (Jetri : Jurnal Ilmiah Teknik Elektro, 2014)
Electronic Road Pricing system is a system that uses GIS technology (Geographic Information System) which serves to locate the vehicle. This project is an ERP (Electronic Road Pricing) system concept simulation based on GPS (Global Positioning System). Rapsberry Pi attached with the GPS sensor has been used to replace the OBU (On Board Unit) so it can receive the GPS signal which will be proceed into coordinates. Those coordinates will be sent to the server and stored into a database. The database served as a storage for user which accessible so that it becomes closer to user (user friendly). An email notification as a feedback system has been used to notify the user that he has entered a paying zone and the money transaction has been made. The simulation test shown that the data obtained was not accurate due to the accuracy of GPS sensor about 10 m. An improvement process has been made to the coordinate data using Polynomial Interpolation approach, so it can be improved by 0.6 m from the maximum missed distances 4.2 m to 3.6 m. Keywords: ERP, GPS, OBU, Rapsberry Pi, Data BaseSistem pembiayaan jalan elektronik adalah sebuah sistem yang menggunakan teknologi GIS (Geographic Information System) untuk mengetahui lokasi kendaraan. Simulasi penelitian dengan konsep ERP (Electronic Road Pricing) berbasis GPS (Global Positioning System). Raspberry Pi yang disambungkan pada sensor GPS berfungsi untuk menggantikan OBU (On Board Unit) sehingga dapat menerima sinyal GPS dan mengubahnya ke dalam bentuk koordinat. Koordinat-koordinat tersebut akan dikirim ke sebuah server dan disimpan pada basis data. Basis data digunakan sebagai tempat penyimpan data sehingga dengan mudah dapat digunakan oleh pengguna. Untuk memberitahu pengguna bahwa ia telah memasuki daerah berbayar dan telah terjadi transaksi keuangan digunakan notifikasi email. Dari pengujian simulasi diketahui bahwa data yang didapat tidak tepat karena ketelitian sensor GPS sekitar 10 m. Perbaikan data koordinat dibuat dengan cara pendekatan interpolasi polinomial sehingga koordinat dapat diperbaiki dengan ketelitian sampai 0,6 m dari selisih jarak 3,6 m sampai 4,2 m. Kata kunci: ERP, GPS, OBU, Rapsberry Pi, Basis Data